Evaluación de las emisiones de N2O provenientes de excretas bovinas en un sistema pastoril - Banegas, Natalia Romina; Viruel, Emilce; Grucci, María Victoria; Beltran, Marcelo Javier; Cosentino, Vanina Rosa Noemi (Asociación Argentina Ciencias del Suelo (AACS), 2024)
Ponencia y poster